AML presenting as bilateral proptosis with lacrimal glands involvement in a young male - Wani, Raashid Maqbool; Rashid, Sabia; Mir, Adil Majeed; Suraya, Saqib (International Journal of Medical Research and Review, 2015)
Acute Myeloid Leukemia (AML) is associated with acquired genetic alterations that result in the replacement of normal marrow elements by relatively undifferentiated blast cells exhibiting one or more types of early myeloid differentiation. Bilateral proptosis with involvement of lacrimal glands and papilledema due to acute myeloid leukemia is presented in this case report. Investigations like complete blood count, peripheral blood film along with bone marrow examination helps in reaching the diagnosis early and a timely intervention thereby increasing the survival chances in such patients.